The Growth and Yield of Shallots and Melons Based on the Interseasonal Windbreaks Cropping System in Anticipation of Climate Change - Saparso; Sudarmaji Arief; Bachtiar Musthafa Muhammad; Tamad (E3S Web of Conferences)
Melon is one of the fruits favored by Indonesian people, as well as shallots which are often used as a spice for Indonesian cuisine. The demand for these two commodities are increased continuously, but the land for agriculture purpose is limited. Utilization marginal land of coastal sand is a solution to deal with increasingly limited agricultural land. Marginal land of coastal sand has limiting factors such as high wind speed that carrying salt which can cause salinity stress for plants. In addition, it is necessary to add soil amendments such as manure and clay to improve soil structure. The purpose of this study was to distinguish the effect of season types, windbreak types, and types of plants used on the growth and yield of melon and shallot plants on coastal land, and to determine the interaction between season types, windbreak types, and plant types on growth and yields of melon and shallot. This study used a Completely Randomized Block Design (CRBD) of Split-Split Plots with three factors and three replications. The first factor is the type of season (dry and rain). The second factor is the type of windbreaker (without windbreaker, 1.5 m plastic windbreaker, 3 rows corn windbreaker, alley corn windbreaker). The third factor is the type of plant [salinity sensitive plants (melon) and salinity resistant plants (shallots)]. The result of the observation data were observed by means of variance and the Duncan’s Multiple Range Test (DMRT) 5% test was performed. The variables observed in the plant growth component were plant height, number of leaves, leaf area, fresh weight of root, fresh weight of plants, and dry weight of plants. The variables observed in the plant yield components were fresh weight of tubers, fresh weight of fruits, and crop yield. There is an interaction between the seasonal factor and the type of plant on the variables of fresh weight of tubers. There is an interaction between the types of windbreakers and the types of plants on the variables of fresh weight of root, fresh weight of tubers, dry weight of plants. There is an interaction between the type of season and the type of wind break in melon and shallot plants in almost all the observed variables. The 1.5 m plastic windbreaker is more effective in the rainy season on melon and shallot plants. This is because during the dry season the level of salinity is higher (0,74 mS/cm) than the rainy season (0,61 mS/cm). Plastic windbreakers are the highest windbreakers and can reduce wind speed which carries salt particles on salinity-sensitive melon plants and salinity-resistant shallot plants.